The horizon book of makers of modern thought (American Heritage, 1972)
This book with some of the great movers of images in the mind, the monumental thinkers of the modern period. These men laid the imaginary mental rails along which our thoughts travel, though we are frequently unaware of how directed we are by these" Makers of Modern Thought". In spire of these men being dead, they live in our minds, in a most contemporary fashion,...